Konsep Sistem Pembiayaan dan Administrasi Keuangan Dalam Lingkup Pendidikan - Nuraini, Nuraini (MADINAH, 2016)
Financial problems are a pretty basic problem in school. Because all the components of education in school are closely related to the financial component of the school. Although not entirely, financial problems will directly affect the quality of schools, especially with regard to facilities, infrastructure and learning resources. Many schools are not able to do teaching and learning activities optimally, just because of financial problems, Both to teach teachers and even for school operational activities are in dire need of funds are not small. Thus, by knowing the concept of financing system as well as financial management and financial administration is very necessary to be known by practitioners of financial management at school institutions.